The effect of salt-drought stress on the growth and physiological characteristics of Viola tricolor seedlings - Liu, Wenlan; Huang, Mengting; Tang, Hong; Han, Rong; Luo, Yongzhong (Frontiers in Plant Science, 2025)
To elucidate the impact of varying degrees of salt, drought, and their combined stress on the physiological and biochemical attributes of Viola tricolor seedlings, a pot culture study was conducted. The experiment utilized Viola tricolor seedlings as test materials, segregated into 16 treatments: four levels of NaCl (0%, 0.2%, 0.4%, 0.6%) for salt stress; four increments in soil field capacity (80%, 65%, 50%, 35%) for drought stress; and combinations of these stresses to assess their cumulative effects. A control group was established using 0% NaCl and 80% field capacity water content. Growth metrics and physiological indicators were quantified under each condition. Results indicate that with escalating degrees of salt and drought stresses, height, dry weight of above-ground parts, dry weight of below-ground parts, and root-to-shoot ratio exhibit an incremental pattern initially followed by a decline. Relative water content decreases, while Malondialdehyde (MDA) content, soluble protein (SP) content, soluble sugars (SS) content, and proline (Pro) content ascend. The activity of peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD) peaks before declining. However, POD remains elevated under 0.6% NaCl and 35% field capacity under severely stressed conditions compared to the control. Chlorophyll content shows a similar rising and then falling trend. POD emerges as the primary antioxidant enzyme in Viola tricolor seedlings when faced with high-salt and severe drought stress. Fuzzy logic analysis suggests that Viola tricolor seedlings demonstrate partial tolerance to moderate salt-drought stress combinations, indicating some cross-adaptation. Specifically, Viola tricolor seedlings exhibit the highest resistance to salt-drought stress under the treatment of 0.2% NaCl and 65% field capacity.